Analisa Spektroskopi Inframerah Transformasi Fourier dan Gas Terlarut Terhadap Perubahan Gugus Fungsi Komposisi Minyak Ester - Saepul Rahmat; Suwarno Suwarno (Infotekmesin, 2020)
This study is conducted to figure out the change in the function of ester oil as a result of the aging process - Kraft paper composite insulation. To duplicate actual conditions on a transformer, a sample of 800 ml biodiesel oil and 6 grams of Kraft paper were put together in a heat-resistant bottle. The sample was put under the same initial conditions through heating at 100 ° C for 24 hours. After initial conditions, then all samples of thermal were accelerated from 336 hours to 672 hours at 120 0C and 150 0C for actual conditions in the transformer. FTIR and DGA test are carried out at each aging period. The aging process shows several changes in functional groups in the ester oil and produced several dominant combustible gas compositions, including carbon monoxide (CO) and ethane (C2H6). These flammable gases arise due to the decomposition of the insulation which makes C = C functional groups in a particular spectrum produce ethane gas, thereby increasing the bonds of paper insulation.